2018
DOI: 10.1103/physrevd.97.126012
|View full text |Cite
|
Sign up to set email alerts
|

Holographic entropy bound in higher-dimensional spacetimes

Abstract: The celebrated holographic entropy bound asserts that, within the framework of a self-consistent quantum theory of gravity, the maximal entropy (information) content of a physical system is given by one quarter of its circumscribing area: S ≤ S max ¼ A=4l 2 P (here l P is the Planck length). An intriguing possible counterexample to this fundamental entropy bound, which involves homogenous weakly self-gravitating confined thermal fields in higher-dimensional spacetimes, was proposed almost a decade ago. Interes… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 19 publications
0
8
0
Order By: Relevance
“…(61). It is further conjectured that the bound also holds for higher d-dimensions, with the area A being a d − 2 surface A enclosing a d − 1 volume [33].…”
Section: Euler Relationmentioning
confidence: 98%
See 1 more Smart Citation
“…(61). It is further conjectured that the bound also holds for higher d-dimensions, with the area A being a d − 2 surface A enclosing a d − 1 volume [33].…”
Section: Euler Relationmentioning
confidence: 98%
“…We adopt the thermodynamic formalism presented in [29]. We also study the Bekenstein [30] and the holographic [31][32][33] entropy bounds for the d-dimensional shells. We benefit from the result given in [34] where it is shown that to be divergent free quantically black holes must be at the Hawking temperature.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, semiclassical aspects of black hole physics at large D have been a direct focus of [6][7][8][9]. In particular, the Hawking luminosity was explicitly found in [6], and Refs.…”
Section: Connection To Previous Workmentioning
confidence: 99%
“…In particular, the Hawking luminosity was explicitly found in [6], and Refs. [7][8][9] have discussed the relative size of black hole entropy as compared to the entropies of unbound systems of weakly gravitating matter at large D.…”
Section: Connection To Previous Workmentioning
confidence: 99%
See 1 more Smart Citation